Accelerating Success: Systematic Review of Soft Skills Integration in Automotive Vocational Education - Subagja, Rizky Eka; Sukrawan, Yusep; Mahatkarsa, Gilang Ciptadi (Education and Development Research, 2025)
The automotive and motorcycle industries' transformation through Industry 4.0 technologies demands workforce competencies integrating technical expertise with sophisticated soft skills, yet significant gaps persist between industry requirements and graduate competencies. This systematic literature review provides evidence-based guidance for soft skills integration in automotive-motorcycle vocational education by identifying development models, evaluating comparative effectiveness, and exploring industry-academic collaboration roles. Following PRISMA 2020 guidelines, comprehensive search across Scopus database covering 2020-2025 employed rigorous inclusion criteria focusing on empirical studies. The search strategy yielded 394 articles, with 42 high-quality studies selected for analysis. Data extraction used standardized forms with inter-rater reliability (κ = 0.87), while analysis integrated bibliometric analysis, systematic thematic analysis, and quantitative content analysis. Results reveal curriculum integration models demonstrate superior effectiveness compared to modular approaches across all competency domains, with advantages in communication skills (24 percentage points) and teamwork competencies (21 percentage points). Industry-academia collaboration emerges as fundamental catalyst, though implementation gaps exist between current practice (47% structured internships) and industry recommendations (85% target). The evidence-based framework provides immediate guidance for curriculum design, instructor preparation, and partnership development.